2014
DOI: 10.1007/s12155-014-9527-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of process conditions on the density and durability of wheat, oat, canola, and barley straw briquettes

Abstract: The present study is to understand the impact of process conditions on the quality attributes of wheat oat, barley, and canola straw briquettes. Analysis of variance indicated that briquette moisture content and initial density immediately after compaction and final density after 2 weeks of storage are strong functions of feedstock moisture content and compression pressure, whereas durability rating is influenced by die temperature and feedstock moisture content. Briquettes produced at a low feedstock moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 26 publications
4
47
2
Order By: Relevance
“…Tumuluru et al. , in their studies on briquetting of wheat, oat, barley, and canola straws, indicated that increasing the moisture content to 15% (w.b.) and briquetting temperature to 130°C resulted in lower unit density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumuluru et al. , in their studies on briquetting of wheat, oat, barley, and canola straws, indicated that increasing the moisture content to 15% (w.b.) and briquetting temperature to 130°C resulted in lower unit density.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have worked on pelleting and briquetting of biomass by adjusting feedstock moisture content in the range of 7–23% (w.b.) . Some of the recent research articles published in 2014 have reported on pelleting raw, chemically and thermally pretreated biomass at moisture content >23% (w.b.)…”
Section: Introductionmentioning
confidence: 99%
“…One major reason for different concentrations observed for different raw and thermally-pretreated biomass feedstock can be different chemical composition (i.e., woody biomass has higher fatty acids and lignin compared to herbaceous biomass). On the other hand, herbaceous biomasses are lower in lignin and free fatty acids [39,40]. Further research is needed to understand the chemistry behind different quantities of off-gas emissions from different biomass feedstocks.…”
Section: Discussionmentioning
confidence: 99%
“…In lignocellulosic biomass, the presence of lignin within plant material helps to form pellets without adding any binders 18 . Woody biomass has higher lignin content (29-33%) when compared to a herbaceous biomass, which typically consists of 12-16% lignin 4,19 . At lower feedstock moisture contents of about 10-12% (w.b.…”
Section: Introductionmentioning
confidence: 99%